Effectiveness, sustainability and quality. Criticality of the building process in public works in Italy - Maspoli, Rossella (TECHNE - Journal of Technology for Architecture and Environment, 2013)
In the Italian case are outlined, compared to other European countries, in the 2000s, the limits of the policies for the architectural quality and, in parallel, the deficiencies of the technical regulations for public works contracts. Object of analysis and research are intervention strategies to improve the overall quality of the public sector, which concerns the procedures for project technical verification and validation, the development of tools for the implementation of the quality plan, the prospects for process innovation coherent the Regulation of the Public Contracts Code.